Parameter Sensitivity Analysis of the Hydraulic Fracture Growth Geometry in a Deep Shale Oil Formation: An Experimental Study - Shanzhi Shi; Yushi Zou; Lihua Hao; Beibei Chen; Shicheng Zhang; Xinfang Ma; Shipeng Zhang (Geofluids)
The depth of shale oil of Fengcheng Formation in Mahu of Junggar Basin, China, is 4500-5000 m. The horizontal principal stress difference of deep shale reservoir is high, which makes it difficult to form complex fractures during fracturing reconstruction. In order to fully understand the law of hydraulic fracture propagation in the formation during fracturing construction, the anisotropy characteristics and basic reservoir physical parameters (mineral composition and rock strength parameters) of rock were obtained through mineral composition test and indoor rock mechanics test (Brazil splitting test), and it was found that the heterogeneity was strong. The true triaxial fracturing simulation experimental system is used to carry out experimental research on full-diameter core rock samples, and the propagation patterns of hydraulic fractures under the influence of different geological factors (in situ stress difference and natural fractures) and engineering factors (pumping rate and fracturing fluid viscosity) are compared and analyzed. The results show that the in situ stress is the most important factor affecting fracture propagation, which determines the direction and shape of fracture propagation. The natural weak surface (lamina/bedding and natural fractures, etc.) in shale reservoir is an important reason for complex fractures. The nature of the weak plane, occurrence, and in situ stress jointly determine whether the fracture can extend through the weak plane. With the increase of pumping rate (18 mL/min to 30 mL/min), the ability of hydraulic fractures to penetrate layers is continuously enhanced. The horizontal principal stress difference of deep shale reservoir is high, and the low viscosity fracturing fluid (10 mPa·s) tends to activate the horizontal bedding, while the high viscosity fracturing fluid (80 mPa·s) tends to directly penetrate the bedding to form the vertical main fracture. Therefore, the fracturing technology of alternating injection of prehigh viscosity fracturing fluid and postlow viscosity fracturing fluid can be adopted to maximize the complexity of fracturing fractures in deep shale reservoirs. The research results are designed to provide theoretical guidance for prediction of hydraulic fracturing fracture propagation in shale reservoir and have certain reference significance for field construction.